Pengaruh Sistem Administrasi Perpajakan Modern, Pengetahuan Perpajakan Dan Kualitas Pelayanan Fiskus Pada Kepatuhan WPOP - Yunita Sari, Ni Putu; Jati, I Ketut (E-Jurnal Akuntansi, 2019)
This study aims to determine the system of modern tax administration, knowledge, and service quality. Tax facilitator at the East Denpasar Primary Tax Office. The population in this study were all taxpayers registered at the Pratama East Tax Office. The number of samples used in this study were 100 respondents from 76,543 people who were still working at the East Denpasar Pratama Tax Office in 2017. The sample size was calculated based on the formula with incidental sampling technique. Data collection in this study was conducted by questionnaire method. Data analysis techniques that are multiple linear regression analysis. The results of the study show that the modern tax administration system, knowledge, and quality of taxpecting services are positive for the individual taxpayer tax rate. Keywords:  modern taxation, knowledge, fiscus service, compliance